The quality of education as a modern paradigm of preparing future specialists for speciality “Preschool Education” (Pedagogy of Higher and Secondary Education, 2014)
Inshakov A. Ye. The quality of education as a modern paradigm of preparing future specialists for speciality “Preschool Education”.The article is devoted to issues concerning improving grades and the quality of education while training preschool teachers in the course “The modern Ukrainian language workshop”. The suggested system of work and forms of control will help to form language skills that are necessary for a teacher.
Keywords: the quality of education; preschool education; generalization and systematization of knowledge; performance level; information-packed module; the formation of abilities and skills, forms of control performance